(untitled) (Baghdad Science Journal, 2010)
A rapid high sensitive and inexpensive economic method has been developed for the Determination of phenoxazine by using molecular spectrophotometry. The method is based on the oxidation of phenoxazine by potassium (meta)periodate in acidic medium. The oxidation conditions were selected to enhance the sensitivity and the stability of the pink colored species which shows an absorption maximum at 530 nm. The Beer’s law was obeyed for phenoxazine concentration range from 1 to 6 µg mL-1 with 0.003 µg mL-1 detection limit and provided variation coefficients between 0.4 to 1.7 %. This method was successfully applied for the determination of phenoxazine in aqueous samples